Human senescence : evolutionary and biocultural perspectives - Crews, Douglas E. (Cambridge studies in biological and evolutionary anthropology, 2003)
It is only comparatively recently in evolutionary terms that humans have developed late-life survival. Looking at anthropological, gerontological and biocultural evidence, Human Senescence explores why humans age only slowly over our lifespan, and what impacts this has on our health and lives today.